IMPLEMENTASI KEBIJAKAN KOTA LAYAK ANAK DI KOTA PEKANBARU TAHUN 2018 - Putra, Eko Ananda; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Children are the nation’s generation who have the right and obligation of participate in building Indonesia nationalists. Childen are the subject and object of Indonesia nationalist development. The municiple goverment of Pekanbaru, in this case the womens empowerment and child protection office along with other regional apparatus organization have implemented child-friendly city policy in the city of Pekanbaru to fulfill children’s right and protect children from violence.As for the first research objective to describe the implementation of child-friendly city policies in Pekanbaru city in 2018. And the second, to find out what are the in hibiting factor for implementing child-friendly city policies in Pekanbaru city in 2018. The research method used is qualitative research. This type of research is descriptive qualitative. In collecting data the writer uses interview and documentation thecniques.The result of the study show that in 2018 the implementation of child-friendly city policies in the city of Pekanbaru has implemented a child-friendly city policy. But there are still problems found in the field jue to several factors, both from internal sources such as the lock of labor staff in the women’s empowerment and child protection offices. Then external factor such as the poverty rate are still quite high. Keyword : Comunication, Resource, Amenities